Analisis Curah Hujan di Kota Padang dengan Menggunakan Rantai Markov - Ultari Femi Arshinta; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2019)
Abstract– Rainfall is one of the natural phenomena that always changes from one condition to another. If rainfall occurs with high intensity, it can result in natural disasters. One area in West Sumatra that receives high-intensity rainfall is Padang. In this research the Markov chain method is used to determine the results of rainfall analysis for the future. This study is an applied research using secondary data, namely dasarian rainfall data obtained from BMKG Padang Pariaman. For the future it is predicted that areas that have rainfall tend to be high (Water Plan Semen Padang), areas that have rainfall tend to be medium (Bandar Buat, Limau Manih-UNAND, Lubuk Minturun, Muara Palam-Parak Karakah, Nanggalo, Tambang Semen Padang, dan Teluk Bayur) and the probability for rainfall that falls for Padang tends to be medium. Keywords– Markov Chain, Matrix Transition Probability, Rainfall.